Studi Dampak Perairan Dangkal terhadap Gaya Lateral (Sway Force) dan Momen Berputar (Yaw Moment) Kapal - Rico; Fakhri Akbar Ayub (Applied Science and Technology on Naval Engineering, 2025)
This study investigates the influence of restricted waters on the sway force (Y’H) and yaw moment (N’H) acting on a ship. We performed simulations using Computational Fluid Dynamics (CFD) on a 1:40 scale KRISO Container Ship (KCS) model, varying ship speed, water depth (1.3T and 1.6T), and drift angle (2°–10°). The simulation results indicate that both Y’H and N’H increase significantly as the water becomes shallower and the drift angle becomes larger. This phenomenon is attributed to the pressure imbalance around the ship's hull, caused by flow confinement. These findings are anticipated to provide valuable insights for safer and more efficient ship maneuvering, especially in narrow and shallow waterways. Keywords: restricted waters; bank effect; sway force; yaw moment; CFD